A laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient and a preparation method thereof
Patent Information
- Application Number
- CN202311641187.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-01
AI Technical Summary
但是,MoS2在激光熔覆过程中易发生分解,不易保留至涂层,达不到预期减磨效果
[0020] This invention relates to a laser cladding layer with a high self-lubricating molybdenum disulfide phase and low friction coefficient. The cladding material uses molybdenum disulfide and iron-based alloy powder, resulting in low cost. During laser cladding, molybdenum disulfide agglomerates into a MoS2 phase at high energy density, exhibiting excellent room-temperature lubrication properties. Furthermore, the MoS2 phase forms a complete and continuous lubricating film during wear. The resulting laser cladding layer with a high self-lubricating MoS2 phase and low friction coefficient exhibits a low friction coefficient and low wear weight loss. Example results show that molybdenum disulfide is uniformly dispersed in the cladding layer in particle form, and the MoS2 phase forms a complete and continuous lubricating film during friction and wear, reducing the wear rate by more than 80%.
Smart Images

Figure CN117721458B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating protection technology, specifically relating to a laser cladding layer with a high molybdenum disulfide self-lubricating phase and a low friction coefficient, and its preparation method. Background Technology
[0002] Friction and wear are among the main failure modes affecting material properties. Low-carbon steel is widely used in petroleum, bridges, vehicles, and other fields. However, due to its low hardness and poor wear resistance, low-carbon steel's use under various wear conditions is severely limited. With technological advancements and accelerated industrialization, reducing workpiece wear and improving the wear performance of parts is particularly urgent.
[0003] Currently, various surface modification techniques have been used to prepare alloy coatings with different compositions. Laser cladding can produce dense coatings with good metallurgical bonding. However, iron-based alloy coatings still cannot meet the performance requirements of mechanical parts in complex environments. Therefore, improving coating hardness and reducing the coefficient of friction to enhance wear resistance is widely adopted. Adding hard phases such as WC and TiC to the coating can effectively improve its wear resistance. However, the addition of these hard phases also increases the coating's crack sensitivity, posing challenges to the surface modification process. To further improve the coating's wear resistance and reduce crack sensitivity, MoS2 solid lubricant has been added to the alloy powder. However, MoS2 is prone to decomposition during laser cladding and is not easily retained in the coating, failing to achieve the desired friction reduction effect. Summary of the Invention
[0004] To address the problems existing in the prior art, the present invention aims to provide a laser cladding layer with a high molybdenum disulfide self-lubricating phase and a low friction coefficient, and a method for preparing the same. The self-lubricating laser cladding layer rich in MoS2 provided by the present invention has good self-lubricating properties and exhibits a low friction coefficient and wear rate.
[0005] The technical solution adopted in this invention is as follows:
[0006] A laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient comprises, by mass percentage: 88%–96% iron-based alloy powder and 4%–12% molybdenum disulfide powder.
[0007] Preferably, the iron-based alloy powder has a particle size of 50–150 μm.
[0008] Preferably, the particle size of the molybdenum disulfide is 10–40 μm.
[0009] Preferably, the mass percentage of MoS2 phase in the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient is 2.0% to 7.1%.
[0010] Preferably, the iron-based alloy powder comprises, by mass percentage: Fe 75%-80%, Cr 5%-10%, Co 6%-10%, and Ni 5%-8%.
[0011] The method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient as described above includes the following steps:
[0012] The raw materials of the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient are mixed to obtain a mixture;
[0013] The mixture is laser-clad onto the substrate surface to obtain the high molybdenum disulfide self-lubricating phase low friction coefficient laser cladding layer;
[0014] The control parameters for laser cladding include: powder feeding rate of 0.2–1.0 g / s, laser power of 800–1000 W, scanning speed of 3–6 mm / s, and defocusing amount of +2 mm.
[0015] Preferably, the raw materials of the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient are mixed by ball milling, and the ball milling method is dry ball milling.
[0016] Preferably, stainless steel grinding balls are used for ball milling, with a diameter of 3-20 mm, a ball-to-material ratio of (8-10):1, a milling rate of 100-300 r / min, and a milling time of 10-60 min.
[0017] Preferably, the preparation method of the present invention further includes a drying process of the mixture, wherein the drying temperature is 110-130°C and the drying time is 3-4 hours.
[0018] The present invention also provides a composite material comprising a matrix and a laser cladding layer clad on the surface of the matrix, wherein the laser cladding layer is prepared by the preparation method of the present invention as described above.
[0019] The present invention has the following beneficial effects:
[0020] This invention relates to a laser cladding layer with a high self-lubricating molybdenum disulfide phase and low friction coefficient. The cladding material uses molybdenum disulfide and iron-based alloy powder, resulting in low cost. During laser cladding, molybdenum disulfide agglomerates into a MoS2 phase at high energy density, exhibiting excellent room-temperature lubrication properties. Furthermore, the MoS2 phase forms a complete and continuous lubricating film during wear. The resulting laser cladding layer with a high self-lubricating MoS2 phase and low friction coefficient exhibits a low friction coefficient and low wear weight loss. Example results show that molybdenum disulfide is uniformly dispersed in the cladding layer in particle form, and the MoS2 phase forms a complete and continuous lubricating film during friction and wear, reducing the wear rate by more than 80%.
[0021] In the preparation of the laser cladding layer with high MoS2 self-lubricating phase and low friction coefficient of the present invention, the control parameters during laser cladding include: powder feeding rate of 0.2-1.0 g / s, laser power of 800-1000 W, scanning speed of 3-6 mm / s, and defocusing amount of +2 mm. Based on the coating raw material of the present invention, the MoS2 self-lubricating phase can be retained in the coating with extremely low heat input, thus preparing a cladding layer with high MoS2 self-lubricating phase and low friction coefficient. Molybdenum disulfide is uniformly dispersed in the cladding layer in the form of particles. During the friction and wear process, the MoS2 phase forms a complete and continuous lubricating film, which can effectively reduce the wear rate. Attached Figure Description
[0022] Figure 1 This is a wear morphology diagram of the iron-based alloy cladding layer;
[0023] Figure 2 This is a wear morphology diagram of the cladding layer in Embodiment 1 of the present invention;
[0024] Figure 3 This is a wear morphology diagram of the cladding layer in Embodiment 2 of the present invention;
[0025] Figure 4 This is a wear morphology diagram of the cladding layer in Embodiment 3 of the present invention. Detailed Implementation
[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0027] The raw materials for the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low coefficient of friction of the present invention, by mass percentage, include: 88%–96% iron-based alloy powder; and 4%–12% molybdenum disulfide powder; wherein the particle size of the molybdenum disulfide powder is 10–40 μm, and the particle size of the iron-based alloy powder is 50–150 μm. The iron-based alloy powder, by mass percentage, comprises: 75%–80% Fe, 5%–10% Cr, 6%–10% Co, and 5%–8% Ni.
[0028] The method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to the present invention includes the following steps:
[0029] Step 1: Place the iron-based alloy powder, molybdenum disulfide powder, milling jar, and milling balls into an oven and dry them at 110-130℃ for 3-4 hours;
[0030] Step 2: Weigh the iron-based alloy powder and molybdenum disulfide powder according to the ratio and add them to a clean ball mill jar;
[0031] Step 3: Add stainless steel balls with a diameter of 3-20mm into the grinding jar at a ball-to-material ratio of (8-10):1;
[0032] Step 4: Install the grinding jars symmetrically on the ball mill;
[0033] Step 5: Set the ball mill parameters: ball mill speed 100-300 r / min, time 10-60 min.
[0034] Step 6: Place the ball-milled mixed powder into an oven and dry it at 110-130℃ for 3-4 hours;
[0035] Step 7: After obtaining the mixed powder, the mixed powder is placed into the powder feeder and laser cladding is performed. The control parameters during laser cladding include: powder feeding rate: 0.2-1.0 g / s, laser power: 800-1000 W, and scanning speed: 3-6 mm / s.
[0036] The laser cladding layer with high MoS2 self-lubricating phase and low friction coefficient prepared by the above method exhibits good room temperature lubrication performance. Molybdenum disulfide agglomerates into the MoS2 phase under laser light, and the MoS2 phase forms a lubricating film with lubricating effect during wear. The resulting laser cladding layer with high MoS2 self-lubricating phase and low friction coefficient has a low friction coefficient and wear weight loss.
[0037] The laser cladding with the aforementioned low heat input also leads to the decomposition of some MoS2. According to the measurement, the mass percentage of MoS2 phase in the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient is 2.0% to 7.1%.
[0038] Example 1
[0039] By mass percentage, the raw materials for the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low coefficient of friction in this embodiment include:
[0040] Molybdenum disulfide powder: 4%; iron-based alloy powder: 96%; wherein the particle size of the molybdenum disulfide powder is 10–40 μm; and the particle size of the iron-based alloy powder is 50–150 μm. By mass percentage, the iron-based alloy powder comprises: Fe 80%, Cr 8%, Co 7%, and Ni 5%.
[0041] The method for preparing the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient in this embodiment includes the following steps:
[0042] Step 1: Place the iron-based alloy powder, molybdenum disulfide powder, milling jar, and milling balls into an oven and dry them at 120°C for 3 hours;
[0043] Step 2: Weigh the iron-based alloy powder and molybdenum disulfide powder according to the ratio and add them to a clean ball mill jar;
[0044] Step 3: Add stainless steel grinding balls with a diameter of 3-20mm into the grinding jar at a ball-to-material ratio of 8:1;
[0045] Step 4: Install the grinding jars symmetrically on the ball mill;
[0046] Step 5: Set the ball milling parameters: ball milling time is 30 minutes, and rotation speed is 200 r / min;
[0047] Step 6: Place the ball-milled powder into an oven and dry it at 120℃ for 3 hours;
[0048] Step 7: Select a Q345 substrate, use sandpaper to remove the oxide layer and impurities on the Q345 surface, and use acetone to wipe away oil and water stains on the Q345 surface;
[0049] Step 8: Place the mixed powder obtained in Step 6 into the powder feeder and perform laser cladding on the Q345 surface treated in Step 7. The control parameters during laser cladding include: powder feeding rate: 0.2g / s, laser power: 1000W, scanning speed: 3mm / s, defocusing amount: +2mm.
[0050] Step 9: The microhardness and wear amount of the coating and the cladding layer prepared in this embodiment were tested using a hardness tester and a tribometer. The hardness test used a load of 300g and a holding time of 15s. A pin-disc type was used for the wear test, with the sample being a cylindrical specimen with a diameter of 4.8mm and a height of 12.7mm. The friction pair was GCr15. The tribometer test used a load of 50N, a time of 30min, and a rotation speed of 100r / min.
[0051] The coating of this embodiment was tested for hardness and abrasion resistance. The Vickers hardness was 450 HV. 0.3 The coefficient of friction is 0.45, and the wear loss is 7.3 mg.
[0052] Figure 1 The image shows the wear morphology of the iron-based alloy coating without the addition of MoS2. The cladding layer surface exhibits obvious ploughing grooves and plastic deformation morphology, and is rough. Figure 2 The wear morphology of the coating with 4% MoS2 in this embodiment is shown. The furrows become significantly shallower, and plastic deformation gradually becomes less noticeable. Compared to the previous embodiment, the wear weight loss of the coating with 4% MoS2 is reduced by 80%.
[0053] Example 2
[0054] By mass percentage, the raw materials for the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low coefficient of friction in this embodiment include molybdenum disulfide powder: 8%; iron-based alloy powder: 92%; wherein,
[0055] The particle size of the molybdenum disulfide powder is 10–40 μm; the particle size of the iron-based alloy powder is 50–150 μm. By mass percentage, the iron-based alloy powder comprises: Fe 80%, Cr 8%, Co 7%, and Ni 5%.
[0056] The method for preparing the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient in this embodiment includes the following steps:
[0057] Step 1: Place the iron-based alloy powder, molybdenum disulfide powder, milling jar, and milling balls into an oven and dry them at 120°C for 4 hours;
[0058] Step 2: Weigh the iron-based alloy powder and molybdenum disulfide powder according to the ratio and add them to a clean ball mill jar;
[0059] Step 3: Add stainless steel grinding balls with a diameter of 3-20mm into the grinding jar at a ball-to-material ratio of 8:1;
[0060] Step 4: Install the grinding jars symmetrically on the ball mill;
[0061] Step 5: Set the ball milling parameters: ball milling time is 30 minutes, and rotation speed is 200 r / min;
[0062] Step 6: Place the ball-milled powder into an oven and dry it at 120℃ for 4 hours;
[0063] Step 7: Select a Q345 substrate, use sandpaper to remove the oxide layer and impurities on the Q345 surface, and use acetone to wipe away oil and water stains on the Q345 surface;
[0064] Step 8: Place the mixed powder obtained in Step 6 into the powder feeder and perform laser cladding on the Q345 surface treated in Step 7. The control parameters during laser cladding include: powder feeding rate: 0.2g / s, laser power: 1000W, scanning speed: 3mm / s, defocusing amount: +2mm.
[0065] Step 9: The wear of the coating and the cladding layer prepared in this embodiment was tested using a hardness tester and a friction and wear testing machine. A pin-disc type was selected for the wear test. The cladding layer sample was a cylindrical sample with a diameter of 4.8 mm and a height of 12.7 mm. The friction pair was GCr15. The friction and wear test was conducted with a load of 50 N, a time of 30 min, and a rotation speed of 100 r / min.
[0066] The coating of this embodiment was tested for hardness and abrasion resistance. The Vickers hardness was 445 HV. 0.3 The coefficient of friction is 0.43, and the wear loss is 5.5 mg.
[0067] Figure 3 The wear morphology of the coating when 8% MoS2 is added in this embodiment. (Compared to...) Figure 1 , Figure 2 In comparison, the furrows became shallower and a MoS2 lubrication zone (black area) appeared. Compared with the wear weight loss of pure iron-based coatings, the wear weight loss of the coating was reduced by 85% when 8% MoS2 was added.
[0068] Example 3
[0069] By mass percentage, the raw materials for the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low coefficient of friction in this embodiment include: molybdenum disulfide powder: 12%; iron-based alloy powder: 88%; wherein the particle size of the molybdenum disulfide powder is 10–40 μm; and the particle size of the iron-based alloy powder is 50–150 μm. By mass percentage, the iron-based alloy powder comprises: Fe 80%, Cr 8%, Co 7%, and Ni 5%.
[0070] The method for preparing the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient in this embodiment includes the following steps:
[0071] Step 1: Place the iron-based alloy powder, molybdenum disulfide powder, milling jar, and milling balls into an oven and dry them at 120°C for 4 hours;
[0072] Step 2: Weigh the iron-based alloy powder and molybdenum disulfide powder according to the ratio and add them to a clean ball mill jar;
[0073] Step 3: Add stainless steel grinding balls with a diameter of 3-20mm into the grinding jar at a ball-to-material ratio of 10:1;
[0074] Step 4: Install the grinding jars symmetrically on the ball mill;
[0075] Step 5: Set the ball milling parameters: ball milling time is 30 minutes, and rotation speed is 200 r / min;
[0076] Step 6: Place the ball-milled powder into an oven and dry it at 120℃ for 4 hours;
[0077] Step 7: Select a Q345 substrate, use sandpaper to remove the oxide layer and impurities on the Q345 surface, and use acetone to wipe away oil and water stains on the Q345 surface;
[0078] Step 8: Place the mixed powder obtained in Step 6 into the powder feeder and perform laser cladding on the Q345 surface treated in Step 7. The control parameters during laser cladding include: powder feeding rate: 0.2g / s, laser power: 1000W, scanning speed: 3mm / s, defocusing amount: +2mm.
[0079] Step 9: The wear of the coating and the cladding layer prepared in this embodiment was tested using a hardness tester and a friction and wear testing machine. A pin-disc type was selected for the wear test. The cladding layer sample was a cylindrical sample with a diameter of 4.8 mm and a height of 12.7 mm. The friction pair was GCr15. The friction and wear test was conducted with a load of 50 N, a time of 30 min, and a rotation speed of 100 r / min.
[0080] The coating of this embodiment was tested for hardness and abrasion resistance. The Vickers hardness was 460 HV. 0.3 The coefficient of friction is 0.28, and the wear loss is 2.8 mg.
[0081] Figure 4 The wear morphology of the coating when 12% MoS2 is added in this embodiment. Figure 1 In comparison, the furrows become shallower, and there is virtually no obvious plastic deformation on the surface. Compared to the wear weight loss of pure iron-based coatings, the wear weight loss of the coating with the addition of 12% MoS2 is reduced by 93%.
[0082] It should be noted that the above-described embodiments are merely preferred embodiments of the present invention. Besides the above embodiments, the present invention has many other embodiments. All technical solutions formed by equivalent substitutions fall within the scope of protection claimed by the present invention.
Claims
1. A laser cladding layer with a high molybdenum disulfide self-lubricating phase and a low coefficient of friction, characterized in that, By mass percentage, its raw materials include: iron-based alloy powder: 88%~96%, molybdenum disulfide powder: 4%~12%; The iron-based alloy powder comprises: Fe 80%, Cr 8%, Co 7%, Ni 5%; The mass percentage of MoS2 phase in the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient is 2.0%~7.1%. The method for preparing the laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient includes the following steps: The raw materials of the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient are mixed to obtain a mixture; The mixture is laser-clad onto the substrate surface to obtain the high molybdenum disulfide self-lubricating phase low friction coefficient laser cladding layer; The control parameters for laser cladding include: powder feeding rate: 0.2~1.0g / s, laser power: 800~1000W, scanning speed: 3~6mm / s, and defocusing amount: +2mm; The substrate is made of low-carbon steel.
2. The laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to claim 1, characterized in that, The iron-based alloy powder has a particle size of 50~150μm.
3. The laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to claim 1, characterized in that, The particle size of the molybdenum disulfide is 10~40μm.
4. A method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to any one of claims 1-3, characterized in that, The process includes the following: The raw materials of the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient are mixed to obtain a mixture; The mixture is laser-clad onto the substrate surface to obtain the high molybdenum disulfide self-lubricating phase low friction coefficient laser cladding layer; The control parameters for laser cladding include: powder feeding rate of 0.2~1.0g / s, laser power of 800~1000W, scanning speed of 3~6mm / s, and defocusing amount of +2mm.
5. The method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to claim 4, characterized in that, The raw materials of the laser cladding layer with high molybdenum disulfide self-lubricating phase and low friction coefficient are mixed by ball milling, and the ball milling method is dry ball milling.
6. The method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to claim 5, characterized in that, Stainless steel grinding balls are used in the ball milling process. The diameter of the stainless steel grinding balls is 3~20mm, the ball-to-material ratio is (8~10):1, the ball milling speed is 100~300r / min, and the time is 10~60min.
7. The method for preparing a laser cladding layer with a high molybdenum disulfide self-lubricating phase and low friction coefficient according to claim 4, characterized in that, It also includes a process of drying the mixture, where the temperature is 110~130℃ and the time is 3~4 hours.
8. A composite material, characterized in that, The composite material includes a matrix and a laser cladding layer clad on the surface of the matrix, wherein the laser cladding layer is prepared by the preparation method according to any one of claims 4-7.